KARAKTERISTIKA TANAMAN LEGUME PADA FASE VEGETATIF - Rusmana Rusmana; Ratna Fitri Yenny (Jurnal Agroekoteknologi, 2014)
This study was conducted to determine the pattern characteristics of legumes in the vegetative phase by using the Relative Growth Rate, Net Assimilation Rate (LAB), and Leaf Area Ratio (LTR). Where the LTR is dry matter production efficiency index, is a measure of the efficiency of clean LAB leaf area and the NLD is the quotient of leaf area to total plant dry weight. The experiment was conducted in field trails and laboratory PandeglangSMKN 2 Faculty of Agriculture, University of Sultan AgengTirtayasa. Starting in September to December 2012. Trial ordered by a single factor randomized complete block design (legume crops). Type of legume crops are planted consist of the three types, namely : soy beans, green beans, and peanuts. For purposes of analysis vegetative growth phase was observed (destructive) six times. The result showed that the characteristics of three types of legume crops : soy beans, peanuts, green  beans, and each has different characteristics. Where the LTR and LAB in legumes has decreased, and the soy bean crop legumes NLD slightly increased, while the peanuts and green beans decreased with increasing age of the plant.